Effect of training on the physiological factors of performance in elite marathon runners (males and females - Billat, V.; Demarle, A.; Paiva, M.; Koralsztein, J. P. (International Journal of Sports Medicine, 2002)
This study examined the effect of 8 weeks of specific marathon training before the Olympic trials on the physiological factors of the marathon performance in top-class marathon runners. Five males and four females, age 34 +/- 6 yr (+/- SD) with a marathon performance time of 2 h 11 min 40 s +/- 2 min 27 s for males and 2 h 35 min 34 s +/- 2 min 54 s for females, performed one test ten and two weeks before the trials. Between this period they trained weekly 180 +/- 27 km and 155 +/- 19 km with 11 +/- 7 and 7 +/- 0 % of this distance at velocity over 10000 m for males and females, respectively. The purpose of this test was to determine in real conditions i. e. on level road: Vdot;O 2 peak, the energy cost of running and the fractional utilisation of Vdot;O 2 peak at the marathon velocity (vMarathon). They ran 10 km at the speed of their personal best marathon performance on a level road and after a rest of 6 min they ran an all-out 1000 m run. Vdot;O 2 peak increased after the 8 weeks of pre-competitive training (66.3 +/- 9.2 vs 69.9 +/- 9.4 ml x min (-1) x kg (-1), p = 0.01). Moreover, since the oxygen cost of running at vMarathon did not change after this training, the fractional utilization (F) of Vdot;O 2 peak during the 10 km run at vMarathon decreased significantly after training (94.6 +/- 6.2 % Vdot;O 2 peak vs 90.3 +/- 9.5 % Vdot;O 2 peak, p = 0.04). The high intensity of pre-competitive training increased Vdot;O 2 peak and did not change the running economy at vMarathon and decreased the fractional utilization of Vdot;O 2 peak at vMarathon.